The Reaction of The Indonesian Capital Market to The Implementation of Covid-19 Emergency Large Scale Social Restriction - Riza Farid; Bambang Widagdo; Muhammad Jihadi (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
This research purpose to discover and determine the conditions in the Indonesian capital market regarding the implementation of the Covid-19 Pandemic Emergency Large-Scale Social Restrictions (PSBB) at April 10, 2020. This study uses an event study type of research which aims to examine the information content which is happening to the capital market. The indicators in this study are using Average Abnormal Return (AAR) and Average Trading Volume Activity (ATVA). The observation period in this study was 11 working days on the Indonesia Stock Exchange with 3 types, namely 5 days before the implementation of the Covid-19 Pandemic Emergency PSBB, 1 day on the event date, and 5 days after the Covid-19 Pandemic Emergency PSBB implementation. The character of this research is comparative, namely comparing an indicator from before and after the event took place. This study uses the LQ45 Index population with a sample of 45 stocks in the period August 2021-January 2022. The results of this study indicate that the implementation of the Covid-19 Pandemic Emergency PSBB, April 10, 2020, has no effect on Average Abnormal Return (AAR) and Average Trading Volume Activities (ATVA).